Maternal knowledge, attitude and practices during childhood diarrhoea. (October 2018) - Dhingra, Dhulika; Dabas, Aashima; Anand, Tanu; Pinnamaneni, Ramya
Diarrhoea and pneumonia account for most deaths in children aged < 5 years. However, most diarrhoeal deaths are preventable with appropriate hygienic measures and timely initiation of rehydration therapy. A cross-sectional study was conducted on 280 mothers with children aged 2–59 months with acute watery diarrhoea at a tertiary hospital. One-fifth of respondents were illiterate and only one-third of mothers pre-treated water to make it drinkable. Mean knowledge scores for hand washing, diarrhoea prevention and complications of diarrhoea were poor, though higher in educated mothers ( P  < 0.05). Scores were similar for the first episode or repeat episodes of diarrhoea. Only 50.4% and 55.2% mothers knew the correct method of Oral Rehydration Solution (ORS) preparation and administration, respectively. Lack of adequate maternal knowledge and practices concerning childhood diarrhoea highlights the need for patient counselling and education, especially among the illiterate in India.